Eksplorasi faktor-faktor yang mempengaruhi kepuasan pelanggan Barberking Cabang Puri Anjasmoro di Kota Semarang - Kurniawan, Yoga Rizky; Putra, Febrianur Ibnu Fitroh Sukono; Chasanah, Amalia Nur; Ulfa, Adilla Kustya (Nur Science Institute, 2025)
This study aims to analyze the influence of brand image, service quality, and price perception on customer satisfaction at Barberking Barbershop in Semarang City. This analysis represents a strategic initiative to enhance competitiveness and maintain customer loyalty in the face of intense competition within the barbershop service industry. A quantitative approach was employed in this study, utilizing a field survey in the form of a questionnaire with a Likert Scale. The sampling technique used was non-probability (purposive sampling), with a sample size of 100 respondents. The analysis tool for this study was multiple linear regression. The findings indicate that brand image does not significantly influence customer satisfaction at Barberking Barbershop in Semarang City. In contrast, service quality and price perception had a significant impact on customer satisfaction. Further analysis revealed that 72% of the variability in customer satisfaction can be explained by the three independent variables: brand image, service quality, and price perception. Improvements in service aspects such as cleanliness, security, staff friendliness, and responsiveness to customer complaints are recommended to enhance customer satisfaction.